Understanding how family demands impair health behaviors in working sole mothers: The role of perceived control over leisure time. Issue 2 (7th September 2021) - Calderwood, Charles; Minnen, Molly E.; Phetmisy, Cassandra N.; Kidwell, Kate E.; French, Kimberly A.; King, Danielle D.
Abstract: Working sole mothers (i.e., nonpartnered women who work) may experience elevated family demands that impose barriers to pursuing health behaviors during their daily leisure time. We aimed to map the process through which evening family demands influence leisure‐time health behaviors in this priority population of employees, in an effort to identify targets for intervention development and health disparity reduction. Conducting a 7‐day daily survey study in a sample of 102 working sole mothers, we supported perceptions of control over leisure time as a key mechanism linking evening family demands to leisure‐time exercise. Furthermore, we identified the individual difference of present focus (i.e., a tendency to focus on current experiences) as a key factor that alters how evening family demands affect control over leisure time, which ultimately mitigates the detrimental influence of these demands on evening exercise engagement. In contrast, we did not find evidence to support relationships of evening family demands with the health behaviors of leisure time consumption of alcohol or high sugar, high fat foods via control over leisure time. We discuss how our findings advance theory regarding how family demands influence health and inform practical efforts to reduce health disparities that working sole mothers face.